Malaysia cyber fraud prevention application: features and functions - Looi, Xue Ying; Azana Hafizah Mohd Aman,; Mohamad Sirajuddin Jalil,; Taha Mohd Omar,; Zainab S. Attarbashi,; Abuzaraida, Mustafa Ali (Penerbit Universiti Kebangsaan Malaysia, 2023)
The advent of technological advancements in the era of globalization has given significant advantages upon developing nations. However, it has also led to certain drawbacks, notably the increase of cybercrimes such as Internet fraud (commonly known as scams). Among the contributing factors to this issue in Malaysia are the low level of public awareness and knowledge regarding cyber fraud prevention and Malaysia's cyber laws. Hence it is crutial to have a medium that can spread the knowledge and at the same time increase the awareness. To support this, an apps is developed, named as National Fraud Prevention Centre (NFPC) application. The NFPC application used methods across diverse platforms, including laptops, smartphones, and tablets, using software such as Android Studio and Firebase. In addition, the Agile Methodology is adopted for the app's development, as it facilitates rapid adaptation to changes, fosters customer involvement, and prioritizes the delivery of high-quality software within tight timeframes. The primary objective of the application is to enhance public awareness regarding various forms of fraudulent activities. Users of the application are also provided with detailed information about the modus operandi of the scam, the types of fraud, and the preventive actions to be taken. With a broader knowledge of these crimes, the public will be able to recognize the early signs of fraud and avoid becoming a victim. Furthermore, the application will serve as a user-friendly reporting channel for individuals encountering suspicious or fraudulent activities. This streamlined reporting process will enable swift intervention by authorities, reducing the incidence of fraud and safeguarding the community against unnecessary financial losses.